A STUDY OF OXIDATION OF COTI BY X-RAY PHOTOELECTRON-SPECTROSCOPY - Garrett, S; Egdell, R; Riviere, J (1991)
The interaction of the alloy CoTi with O2 at room temperature has been studied by angle-resolved X-ray photoelectron spectroscopy (XPS). The surface stoichiometry of CoTi was found to be strongly dependent on surface pretreatment. Argon ion sputtering alone generates a Co-rich surface, whilst annealing at 800-1000 K causes segregation of Ti and associated O from the bulk to produce surface Ti enrichment. Oxygen exposure of roughly stoichiometric annealed CoTi surfaces up to 7500 langmuir results in the build-up of an overlayer which becomes increasingly TiO2-like. The Co 2p peaks in XPS show no chemically shifted oxide components even at the highest exposure. However, the increased inelastic background intensity in this region suggests that the Co is increasingly buried by the Ti oxide overlayer. Oxidation of sputtered CoTi surfaces follows a similar pattern, but with an increased rate of oxidation.